2018
DOI: 10.1177/1759091418775562
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Role of Astroglia in Parkinson Disease by Reducing Oxidative Stress Through Dopamine-Induced Activation of Pentose-Phosphate Pathway

Abstract: Oxidative stress plays an important role in the onset and progression of Parkinson disease. Although released dopamine at the synaptic terminal is mostly reabsorbed by dopaminergic neurons, some dopamine is presumably taken up by astroglia. This study examined the dopamine-induced astroglial protective function through the activation of the pentose-phosphate pathway (PPP) to reduce reactive oxygen species (ROS). In vitro experiments were performed using striatal neurons and cortical or striatal astroglia prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 60 publications
1
58
0
Order By: Relevance
“…Astroglia releases GSH and reduces dopamine‐induced ROS toxicity in Nrf2‐depenent manners. We have found that astroglia protect neurons against dopamine exposure by reducing ROS, while astroglia prepared from Nrf2‐KO mice are incapable of such activity . An in vivo model supports the notion that Nrf2‐KO mice are susceptible to a Parkinson's disease‐like phenotype and that an Nrf2 activator can modify the progression of Parkinson's disease …”
Section: Glucose and Lacatesupporting
confidence: 61%
See 3 more Smart Citations
“…Astroglia releases GSH and reduces dopamine‐induced ROS toxicity in Nrf2‐depenent manners. We have found that astroglia protect neurons against dopamine exposure by reducing ROS, while astroglia prepared from Nrf2‐KO mice are incapable of such activity . An in vivo model supports the notion that Nrf2‐KO mice are susceptible to a Parkinson's disease‐like phenotype and that an Nrf2 activator can modify the progression of Parkinson's disease …”
Section: Glucose and Lacatesupporting
confidence: 61%
“…Of note, the functional activation of neurons increases glucose utilization locally, and both neurons and astroglia contribute to glucose consumption. We have focused on the roles of glucose metabolism, especially glycolysis in astroglia, from the perspective of their supportive aspects in the protection of neurons against oxidative stress . Neuronal energy production is dependent on mitochondrial oxidative metabolism, which produces small amounts of reactive oxygen species (ROS).…”
Section: Glucose and Lacatementioning
confidence: 99%
See 2 more Smart Citations
“…In the context of PD, astroglia plays pivotal roles in disease pathology . A recent report has indeed showed that dopamine‐induced increase in PPP activity in astroglia produced a protective effect on cocultured neurons …”
Section: G6pd and Neurodegenerative Diseasesmentioning
confidence: 99%